Trace Metal Contamination Influenced by Land Use, Soil Age, and Organic Matter in Montreal Tree Pit Soil. Issue 5 (1st September 2013) - Kargar, Maryam; Jutras, Pierre; Clark, O.Grant; Hendershot, William H.; Prasher, Shiv O.
Abstract : The short life span of many street trees in the Montreal downtown area may be due in part to higher than standard concentrations of trace metals in the tree pit soils. The effects of land use, soil organic matter, and time since tree planting in a given tree pit (soil age) were studied with respect to the total concentration of trace metals (Cr, Ni, Cu, Zn, Cd, and Pb) in soil collected from tree pits on commercial and residential streets. Contingency table analysis and multiple linear regression were applied to study how these variables were related to the total concentrations of trace metals in soil. Other variables, such as pH, street width, distance of the tree pit from the curb, and tree pit volume, were also used as input to statistical analysis to increase the analysis' explanatory power. Significantly higher concentrations of Cu, Cd, Zn, and Pb were observed in soils from commercial streets, possibly as a result of heavier traffic as compared with residential streets. Soil organic matter was positively correlated with the concentrations of Cu and Pb, probably due to the ability of organic matter to retain these trace metals. Nickel, Cu, Zn, Cd, and Pb were positively correlated with the soil age presumably because trace metals accumulate in the tree pit soil over time. This knowledge can be helpful in providing soil quality standards aimed at improving the longevity of downtown street trees.